Psychosocial risks at work in employees of a mining company in Arequipa. - José Manuel Calizaya López (2020)
The objective of this research was to measure the situation of exposure to psychosocial risks at work in collaborators according to sociodemographic variables in a mining company in Arequipa. The psychosocial risk self-assessment questionnaire was used in the COPSOQ - ISTAS 21 work, version 1.5, in a sample of 201 collaborators, the study used the quantitative, descriptive - comparative, cross-sectional methodological design. The statistical analysis described that the data do not present a normal distribution, so, according to the results, it was shown that the level of exposure to psychosocial risks is unfavorable, being the worker collaborators in comparison to the employees and officials who present greater problems in the demands. psychological, control over work, social support, double presence and esteem, as well as, according to sex, women have the best results in the dimensions mentioned because they control their work, receive support from colleagues and superiors, and the treatment is appropriate Compared to men, and the correlations on the psychological demands showed that there is a high probability of damaging the physical, mental and social health of the collaborator.